PADANAN BONITA DENGAN KELAS KESESUAIAN LAHAN HUTAN TANAMAN JATI - Riyanto, Heru Dwi (JURNAL LITBANG PROVINSI JAWA TENGAH, 2021)
Bonita's approach to show a quality of a land can be quickly identified in well-managed plantations. Bonita as an assessor of land quality is a soil fertility class on a plantation forest area which is arranged with the parameters of height and age of the stand. If the land has not been managed or has just been planted, it will become a barrier to determine the quality class of the land. So we need the Land Suitability Class (KKL) as another approach besides bonita. The KKL Approach is an approach through direct measurement of environmental parameters. The results of the Land Resource Inventory (ISDL) data from each observation point are systematically processed and classified based on potential and inhibiting properties. This ISDL data analysis will produce KKL class for each observation point. Henceforth KKLs will be classified into 3 classes, namely: S1 (very suitable), S2 (appropriate), S3 (marginal appropriate). To further integrate the two approaches, it is necessary to synchronize the two approaches. The results of the synchronization between bonita and KKL are expected to be able to evaluate teak forest land under any circumstances, either in a state of unplanted land, land with young plants that cannot be evaluated bonitaly. The results of the synctonization are as follows: Bonita 4 – 5 (Very good for teak) = S1 (Very suitable for teak), Bonita 3.5 (Good for teak) = S2 (suitable for teak), The result showed that KKL can be used to assess / evaluate the fertility of teak forest land.